The Role of Tax Consultants as Client Advisors in Facing Tax Disputes: A Phenomenological Approach - Yoel Adinata Tenardi; Anak Agung Gde Satia Utama (Eduvest - Journal of Universal Studies, 2025)
Tax regulations often provide only guidance and not concrete steps, leaving significant room for interpretation by the relevant parties themselves. The DGT and taxpayers frequently disagree when differences arise in the interpretation of tax regulations applied in business processes, often resulting in disputes. In dealing with tax disputes, the role of the consultant as a client advisor emerges as the dominant one, because when facing a tax dispute, the tax consultant acts as an extension of the taxpayer, authorized to help the taxpayer defend their position as someone who has fulfilled their tax obligations appropriately. The purpose of this research is to interpret the role of tax consultants as client companions in dealing with tax disputes, by referring to the code of ethics of tax consultants and their practical experiences. This research employs a phenomenological approach within the framework of qualitative research. In this study, data sources in the form of literature were obtained through digital libraries/electronic libraries, individual full-text journal databases, official websites, and online repositories. The results of this research show that the role of tax consultants as client advisors in addressing tax disputes is very complex and challenging. Tax consultants are not only required to possess strong technical competence in the field of taxation, but must also be able to balance client expectations with moral obligations and professional ethics, as stipulated in the IKPI Code of Ethics.